Graphene growth at low temperatures using RF-plasma enhanced chemical vapour deposition - Aishah Khalid,; Mohd Ambri Mohamed,; Akrajas Ali Umar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The advantage of plasma enhanced chemical vapour deposition (PECVD) method is the ability to deposit thin films at relatively low temperature. Plasma power supports the growth process by decomposing hydrocarbon to carbon radicals which will be deposited later on metal catalyst. In this work, we have successfully synthesis graphene on Ni and Co films at relatively low temperature and optimize the synthesis conditions by adjusting the plasma power. Low temperature growth of graphene was optimized at 600°C after comparing the quality of as-grown graphene at several temperatures from 400 to 800°C and by varying plasma powers in the range of 20 - 100 W. Raman analysis of the as-grown samples showed that graphene prefers lower plasma power of 40 W. The annihilation of graphene formation at higher plasma powers is attributed to the presence of high concentration of hydrogen radical from methane which recombines with carbon elements on thin film surface. The optimum graphene growth conditions were obtained at growth temperature of 600°C, plasma power of 40 W and growth time of 10 min with methane flow rate of 120 sccm.